HEGEMONI DALAM NOVEL INDONESIA PARA PRIYAYI KARYA UMAR KAYAM: SEBUAHKAJIAN BUDAYA - Wijaya Heru Santosa (Universitas Sarjanawiyata Tamansiswa, 2014)
This paper contains a study of hegemony in the novel Para Priyayi by Umar Kayam and other forms of hegemony are held by the ruling group. Theory is used to analyze data is the theory of the formation of culture to dominant, residual, and emergent developed by Williams (1989). The results of the study showed that the hegemony contained in the novel The Priyayi is hegemony groups as the dominant group or groups hegemonic to civil society. In the days before World War II, the hegemony committed by the Dutch Government by way of consensus: member high salaries to employees goverment and implement controls to sanction every effort to government employees who read and hang out with people or groups of emergent movement. During the time of World War II hegemony committed by the Japanese government to control strict, militaristic, and miserable priayi and civilians. There is the time of independence, hegemony committed by groups or emergent movement. At era New Order hegemony committed by the military as the dominant group prioritizes strict and authoritarian control. Form of hegemony committed by the dominant form of political hegemony of language, education, and mass media. In the face of the hegemony of the priayi group acts as a group subordinate rulers as dominant hegemonic group.